A review on animal-assisted therapy and activities for healthcare and teaching of children - Myat Min, Myat Min; Cho Cho Zaw, Cho Cho Zaw (Geist Science, 2016)
Children are the future leaders of our society, and their health and well-being are extremely important. Apart from the conventional treatment, the effective therapy for children with physical, mental, social, developmental disorders, and chronic diseases are required to be identified. Thus, finding out the alternative therapy and affectionate way of teaching program especially for the children with special needs are necessary. Animals are members of the community and their latest contribution to human beings come through their assistant activities known as Animal-Assisted Activities (AAA). Animals are also used in Animal-Assisted Therapy (AAT) as a part of Occupational Therapy (OT) which is used for physical and mental development of the children. This study is intended to explore AAT/AAA as useful practices in assisting healthcare and teaching program of children. Online and offline articles, books, and other literature sources on benefits and usage of AAT/AAA are reviewed thoroughly. A number of studies pointed out the positive results of incorporating animals into Pediatric Occupational Therapy, and children teaching programme. The benefits of pet therapy in children are discussed under three main topics namely physical and general healthcare which include pain, illness, trauma and cancer, mental and developmental disorders, and social and educational purpose. According to the findings, the use of pets as AAA, and AAT are highly beneficial to mental, physical, social health and well-being of the children. Hence, the application of it on education and healthcare purpose for children with special needs is strongly recommended.